Ginsenoside Rg1 Prevents Chronic Stress-Induced Depression-Like Behaviors and Neuronal Structural Plasticity in Rats - Hongluan Yu; Cuiqin Fan; Lejin Yang; Shuyan Yu; Qiqi Song; Peng Wang; Xueqin Mao (Cellular Physiology and Biochemistry, 2018)
Background/Aims: Ginsenoside Rg1 has been demonstrated to exhibit neuroprotective effects in various studies. This study aimed to investigate the neuronal mechanisms underlying the neuroprotective and antidepressant-like effects of ginsenoside Rg1 in a rat model of depression. Methods: Chronic unpredictable mild stress was used to induce depression-like behaviors in rats. Transmission electron microscopy was used to observe neuronal synapses within the basolateral amygdala (BLA). The expression of microRNA (miR)-134 in the BLA was verified by real-time quantitative PCR. Finally, the synaptic plasticity-associated proteins CAMP-response element binding protein (CREB) and brain-derived neurotrophic factor (BDNF) were detected by immunoblotting. Results: Results showed that chronic stress effectively induced depression-like behaviors in rats, which were associated with significant ultrastructural changes within BLA neurons. Moreover, chronic stress decreased the expression of miR-134 in the BLA, which was accompanied by decreased phosphorylation of CREB and decreased expression of BDNF. Remarkably, chronic administration of ginsenoside Rg1 (40 mg/kg, i.p., 5 weeks) significantly ameliorated the neuronal structural abnormalities and biochemical changes induced by chronic stress, as well as preventing depression-like behaviors in these rats. Conclusion: Results suggested that ginsenoside Rg1 may exhibit neuroprotection and antidepressant-like effects by activating the CREB-BDNF system within the BLA in this rat model of depression. Amelioration of depression-like behaviors by ginsenoside Rg1 appears to involve modulation of the synapse-associated factor miR-134 within the BLA. Therefore, these findings demonstrate some of the neuronal mechanisms associated with depression and the therapeutic potential of ginsenoside Rg1 for use in the treatment of depression in clinical trials.